1990
DOI: 10.1007/bf01865276
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven nonlinear oscillations of cables

Abstract: Abstract. The objective of this papcr is the study of the d\'namics of damped cable systems, which are suspended in spacc, and their resonance characteristics. Of interest is tile study of the nonlinear behavior of large amplitude forced vibrations in three dimensions. As a lirst-order nonlinear problem the forced oscillations of a system having three-degrees-of-freedom with quadratic nonlinearities is developed in order to consider the resonance characteristics of the cable and the possibility of dynamic inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…He did not identify any Hopf bifurcations and consequently did not study any nonperiodic motions. Tadjbakhsh and Wang [41] investigated the response of wind-driven cables. They modeled the cable as a three-degree-of freedom system with quadratic nonlinearities with the internal resonant conditions w 3 = 20) 2 and 0)2 ~" 20)1.…”
Section: Introductionmentioning
confidence: 99%
“…He did not identify any Hopf bifurcations and consequently did not study any nonperiodic motions. Tadjbakhsh and Wang [41] investigated the response of wind-driven cables. They modeled the cable as a three-degree-of freedom system with quadratic nonlinearities with the internal resonant conditions w 3 = 20) 2 and 0)2 ~" 20)1.…”
Section: Introductionmentioning
confidence: 99%
“…Forced response with coupled vertical and horizontal responses has been analysed in a number of studies based on Galerkin based reduced two-degrees-of-freedom models. Tadjbakhsh and Wang (1990) investigated the response of wind induced cables modelled as a three-degrees-offreedom system including quadratic nonlinearities with the internal resonant conditions ω 3 2ω 2 and ω 2 2ω 1 with the second mode excited (Ω ω 2 ). They found that the system exhibits both saturation and jump phenomena.…”
Section: Stochastic Stability Of Whirling Motion Of a Shallow Cable Umentioning
confidence: 99%
“…The saturation effect may prove useful in the design of materials or structures that absorb [7,8], localize [9][10][11], or divert [12] vibrational or wave energy. The effect can also appear in weakly nonlinear approximations of driven hanging cables [13,14] or spring-pendulum systems [15], in which the relevant couplings contain time derivatives.…”
Section: Introductionmentioning
confidence: 99%